Influencia del material audiovisual en la competencia gestiona responsablemente el espacio y el ambiente en estudiantes de la Institución Educativa Mariscal Oscar R. Benavides, Iquitos 2025 - Navarro Torres, Alexandra Belu (2025)
This study is based on the need to identify whether there is a relationship between the use of audiovisual materials in classes and the improvement of a competence in the area of social sciences, so it was planned to use a non-experimental quantitative descriptive-correlational methodology, The population was all students in 3rd, 4th and 5th grades of high school where the subjects were chosen, and the sample was non-probabilistic and intentional since we worked with students in 4th grade of high school, a total of 136 students, to whom a questionnaire was applied and who were evaluated using a rubric. The most relevant results were that most of the students indicated that the use of audiovisual materials is regular in 50.0% and when evaluating the level of learning achievement, these were in expected achievement with 61.0%, and Spearman's Rho test confirmed the results since it gave a p-value of less than 0.05 in each of the hypotheses raised and it was possible to conclude that there is a relationship between audiovisual materials in the development of the competence in the area of social sciences under study with students of the I. E. M.O.R.B. of the city of Iquitos in the year 2025.